Social Problems in Post-Divorced Single-Parent Families - Kantemirova, Galina (Journal of Sociology: Bulletin of Yerevan University, 2020)
The article examines the influence of divorce on various factors in the life of family members. The works of foreign researchers devoted to environmental factors that affect the likelihood of divorce are analyzed. An assessment of the differences between children from complete and incomplete families is given.
Keywords: Selected:divorce; transmissibility of divorce; post-divorced situation; single-parent family